Pengaruh Pendapatan Asli Daerah, Belanja Modal dan Indeks Pembangunan Manusia - Hobrouw, Yustine Asnad; Suaryana, I Gusti Ngurah Agung; Asri Dwija Putri, I G.A.M. (E-Jurnal Akuntansi, 2021)
This study aims to determine empirically the effect of local revenue on the increase in the human development index in West Papua province and to empirically determine the effect of capital expenditure on the increase in the human development index in West Papua province. The data analysis technique used is multiple linear regression analysis. Based on the results of the analysis, it is known that the Original Regional Income has a positive and significant effect on the increase in the District / City Human Development Index in West Papua Province. This shows that an increase in Regional Original Income (PAD) will tend to increase the Human Development Index. Capital expenditure has a positive and significant effect on increasing the District / City Human Development Index in West Papua Province. Keywords: PAD; Capital Expenditures; Human Development Index.